1998
DOI: 10.1006/jcss.1998.1565
|View full text |Cite
|
Sign up to set email alerts
|

Arity Bounds in First-Order Incremental Evaluation and Definition of Polynomial Time Database Queries

Abstract: After inserting a tuple into or deleting a tuple from a database, a firstorder incremental evaluation system (or a``foies'') for a database query derives the new query answer by using a first-order query on the new database, the old answer, and perhaps some stored auxiliary relations. Moreover, the auxiliary relations must also be maintained similarly using first-order queries.In this paper we measure the space needed by foies in terms of the maximal arity of the auxiliary relations and present results on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Hesse showed that reachability on deterministic graphs can be maintained by quantifier-free update formulas (the corresponding dynamic complexity class is called DynProp), and on undirected graphs with quantifier-free update formulas that can also use auxiliary functions (the corresponding dynamic complexity class is called DynQF) [Hes03b]. Moreover other graph queries such as 2-colorability and the tree-isomorphism query have been studied, and shown to be contained in DynFO [DS98,Ete98].…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Hesse showed that reachability on deterministic graphs can be maintained by quantifier-free update formulas (the corresponding dynamic complexity class is called DynProp), and on undirected graphs with quantifier-free update formulas that can also use auxiliary functions (the corresponding dynamic complexity class is called DynQF) [Hes03b]. Moreover other graph queries such as 2-colorability and the tree-isomorphism query have been studied, and shown to be contained in DynFO [DS98,Ete98].…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
“…Therefore several restrictions of DynFO have been studied, among them the restriction of the arity of auxiliary relations [DS98,DLW03] and syntactic restrictions of first-order update formulas [GMS12]. For a more detailed overview over previous work on lower bounds we refer to Chapter 4, which is devoted to lower bounds and methods for proving them.…”
Section: Maintainability Of Basic Queriesmentioning
confidence: 99%
See 3 more Smart Citations